Cigarette Smoking Sensitizes and Desensitizes Impedance-measured ADP-induced Platelet Aggregation in Whole Blood - Sharp, Dan S; Benowitz, Neal L; Bath, P M W; Martin, John F; Beswick, Andrew D; Elwood, Peter C (Thrombosis and Haemostasis, 1995)
The effect of smoking on platelet aggregation appears to produce conflicting results, with some studies indicating an enhancement and others a decrease of aggregation. This epidemiological study of 120 male smokers, a subset of the Caerphilly Heart Disease Study, examined the relationship of two dimensions of smoking (time proximity of last cigarette before venepuncture and serum nicotine concentration) with threshold dose of adenosine diphosphate (ADP) necessary to induce platelet aggregation in whole blood. Means (range) of ADP threshold dose and nicotine concentration were 1.66 (0.5-2.5, censored) μM and 12.2 (0-35.2) ng/ml. Men smoking within 30 min of venepuncture demonstrated lower ADP threshold doses (-0.48 μM lower [95% C. I.: -0.95, -0.02]) – reflecting increased sensitivity. Men with higher nicotine concentration had higher ADP threshold doses (Regression Coefficient: +0.032 μM per ng/ml [95% C. I.: 0.003, 0.062]) – reflecting decreased sensitivity. Men smoking 30 min or more before venepuncture who also had high nicotine concentration (25-30 ng/ml) demonstrated the highest ADP threshold doses compared to never smokers and to men smoking the previous day (≈2.20 vs 1.86 and 1.81 μM). Relations involving nicotine concentration do not necessarily reflect a pharmacological effect although the potential for a short term nicotine mediated tolerance effect cannot be dismissed. These observations support an hypothesis suggesting a temporal sequence of platelet sensitization and desensitization during smoking.